INISIASI KELOMPOK MASYARAKAT PENGELOLA SAMPAH ORGANIK DENGAN BUDIDAYA MAGGOT BSF (BLACK SOLDIER FLY) DI PADUKUHAN DUKUH, SINDUHRJO, NGAGLIK, SLEMAN, D.I YOGYAKARTA - Astanti, Yuli Dwi; Nandari, Wibiana Wulan; Santoso, Dian Hudawan; Hasanah, Khuswatun; Puryani, Puryani (Dharma: Jurnal Pengabdian Masyarakat, 2023)
Waste is an unresolved government problem. The largest waste collection site (TPS) in Yogyakarta, TPS Piyungan, is starting to get tired of collecting waste from various corners of Yogyakarta. One of the efforts to overcome this problem, the government instructed the Waste Sorting Movement. Based on the Ministry of Environment and Forestry (KLHK), the composition of waste in Indonesia is dominated by organic waste, which reaches 57% of the total landfill. Organic waste can be processed by cultivating BSF Black Soldier Fly (Hermetia Illucens). BSF is a black fly whose maggots (larvae) can degrade organic waste. Maggots (maggots) produced from black fly eggs are very active in eating organic waste. This bioconversion process by maggots can degrade waste more quickly, is odorless, and produces organic compost, and the larvae can be a good source of protein for poultry and fish feed. Maggots have the ability to break down organic waste 2 to 5 times their body weight for 24 hours. One kilogram of maggot can consume 2 to 5 kilograms of organic waste per day. Maggots that have become prepupae and BSF fly carcasses can still be used as animal feed because they are rich in protein. The cocoons can also be used as fertilizer. This process was socialized to Sub Urban groups in the Padukuhan Dukuh, Sidoharjo, Ngaglik, Sleman areas, as a response to the unresolved waste problem. Activities are carried out by: Carrying out outreach related to waste problems and BSF maggot cultivation, Carrying out waste sorting training, Carrying out training on BSF maggot cultivation, Distribution of rubbish bins to residents (partners) as containers to accommodate organic waste, Creation of organic waste storage areas, Construction of BSF Maggot houses , Breeding activities, maintenance and harvesting of BSF maggots, Packaging of BSF Maggot products, Sales of BSF Maggot products